Perancangan Sistem Aplikasi Penilaian Kinerja Karyawan pada PT Bluepay Digital International Berbasis Java - Norman Sasono; Meri Chrismes Aruan; Andri Rahadyan (Teknik Informatika Universitas Pamulang, 2020)
In its implementation, the document recording process carried out by this company is still done manually so that it is not uncommon to find difficulties when processing data. Employee Performance Appraisal Application at Java-based PT.Bluepay Digital International is an organizational process in evaluating employee performance. The purpose of conducting performance appraisals in general is to provide feedback to employees in an effort to improve the appearance of their work and efforts to increase organizational productivity, and specifically carried out in relation to various policies towards employees. Problem limitation is centered on the design of employee performance appraisal applications at Java-based PT.Bluepay Digital International by HRD whose workmanship is still manual to make the application more efficient in evaluating employee performance. The purpose of making an employee performance appraisal application is to provide innovation by using IT technology in processing employee performance appraisals. In making this application using the experimental method so that a good, effective and easy solution can be obtained. The method used is data collection using interview and observation techniques to PT Bluepay Digital International.